Syndrome de Meckel Gruber: à propos d’un cas rare - Itchimouh, Sanaa (Pan Afr Med J, 2016)
Meckel Gruber syndrome is a rare autosomal recessive polymalformation syndrome characterized by occipital encephalocele, polydactyly and cystic renal dysplasia. Ultrasound is, at present, the best tool for prenatal screening of this lethal polymalformation and diagnosys is confirmed by karyotyping. We here report a case of Meckel Gruber syndrome detected by ultrasound. Abortion was performed at 25 weeks of amenorrhoea.